Critical consulting: New perspectives on the management advice industry - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 2002)
A collection of 15 papers by researchers in the field of management consulting. The critical analyses presented here evaluate what management consultants offer, as well as analyzing the emergence of their industry as a contemporary social phenomenon.